Cyclohexane removal and UV post-control of bioaerosols in a combination of UV pretreatment and biotrickling filtration - Sun, Zhirong; Cheng, Zhuowei; Luo, Pengfei; Chen, Jianmeng; Yu, Jianming; Chen, Dongzhi; Zhao, Peng (Frontiers in Environmental Science, 2022)
Biofiltration of hydrophobic and recalcitrant volatile organic compounds faces challenges, and the bioaerosols sourced from the biofiltration might cause secondary pollution. In this study, the combination of ultraviolet photodegradation and biotrickling filtration (UV-BTF) was designed to treat gaseous cyclohexane, and UV post-treatment (post-UV) was further utilized for the bioaerosol emissions management. Results showed that the combined UV-BTF permitted faster biofilm formation and had better removal efficiencies (REs) than the single biotrickling filter (BTF). The maximum elimination capacity (EC) of UV-BTF and single BTF was 4.4 and 1.32 g m−3 h−1, respectively. Carbon balance for the bioreactor showed that both BTF and UV-BTF could convert more than 50% of the initial cyclohexane into microbial biomass. High-throughput sequencing analysis showed that UV-BTF had a richer and more diverse microbial community compared with the single one. The post-UV had a good inactivation effect on the bioaerosols. Not solely the concentrations additionally the particle sizes of the bioaerosols from the post-UV became lower and smaller than those from the single BTF. Microbial analysis showed that UV had a greater impact on the species and quantity of both bacteria and fungi, but mainly on the number of bacteria. Such results suggested that UV could be used as the pretreatment for the enhancement of hydrophobic and recalcitrant VOCs removal in the subsequent biopurification, and also as the post-treatment for the inactivation of some harmful bioaerosols.